Data climate distribution for peninsular Malaysia during El Nino and La Nina [compact disc] - 327873 Rozazila Jumari (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2006